# High School Math (Algebra) Pre-test Quiz

12 Questions | Total Attempts: 1844  Settings Create your own Quiz Most people have a hard time when it comes to Algebra, and most of them give up when it comes to tackling some questions. How good are you when it comes to Algebra? Below is a pretest of basic algebra and arithmetic for high school level mathematics. Do you think you can tackle it? Give it a shot and get to find out!

• 1.
Evaluate: 10 - 2(3)
• A.

-13

• B.

4

• C.

16

• D.

24

• E.

None of the above

• 2.
-23 =
• A.

-8

• B.

-6

• C.

8

• D.

6

• E.

9

• 3.
6 - 32
• A.

-9

• B.

-3

• C.

3

• D.

6

• E.

9

• 4.
Solve for x:3x - 3 = 9
• A.

X = 10x = -6

• B.

X = 6

• C.

X = 4

• D.

X = -6

• E.

None of the above

• 5.
2k + 3 + 5k = 10What should be the first step to solving the equation?
• A.

Substituting values in for k

• B.

Subtracting 5k from both sides of the equation

• C.

Subtracting 2k from 2k and 5k.

• D.

Adding 2k to 5k

• E.

Dividing both sides of the equation by 2

• 6.
2(m - 3) = 3m + 3The first step to solving this equation should be
• A.

Subtracting 3m from both sides of the equation

• B.

Combining 2m with 3m

• C.

Distributing the 2 into (m - 3)

• D.

Subtracting 3 from both sides of the equation

• E.

Substituting values into m

• 7.
Simplify: (2x3)2
• A.

2x^5

• B.

2x^6

• C.

4x^5

• D.

4x^6

• E.

None of the above

• 8.
Write in simplest radical form: sqrt(200)
• A.

10*sqrt(2)

• B.

2*sqrt(10)

• C.

5*sqrt(8)

• D.

100*sqrt(2)

• E.

None of the above

• 9.
What is the slope of the equation,y = -2x + 3
• 10.
What is the y-intercept of the equation,y + 2x = 6
• 11.
What is the value of x in the following system of equations:3x - 2y = 03x + y = 9
• 12.
Solve for x:x2 - x - 2 = 0
Related Topics Back to top
×

Wait!
Here's an interesting quiz for you.